The Rise of Digital Skills Research in the Fourth Industrial Revolution: A Bibliometric Analysis (2015–2025) - Abdul Jalil, Teh Nurul Afiza; Zainol Abidin, Mohd Abidzar; Abd Hamid, Rawiyah (International Review of Management and Marketing, 2026)
This study presents a bibliometric analysis of digital skills research based on 450 Scopus-indexed articles published between 2015 and 2025 in Business, Management, and Accounting. Biblioshiny and VOSviewer were used to identify influential authors, leading journals, institutions, and emerging themes. The analysis reveals an annual publication growth rate of 58.01 per cent, underscoring the increasing importance of digital competencies in workforce development, educational innovation, and economic resilience within the context of the Fourth Industrial Revolution. Keyword co-occurrence highlights clusters related to digital transformation, technology adoption, digitisation, e-learning, and the digital divide, reflecting how organisations and societies incorporate digital capabilities. Bibliometric coupling identifies the intellectual influence of scholars such as Perez-Amaral, Lopez, and Garin-Munoz, while journals including Technological Forecasting and Social Change and Technology in Society emerge as central platforms for disseminating this research. Geographical analysis highlights significant contributions from Spain, Italy, and Indonesia, illustrating both global engagement and regional priorities. The COVID-19 pandemic further accelerated digital transformation, intensifying the urgency of digital upskilling. This review synthesises the evolution, structure, and gaps of digital skills research and provides guidance for scholars, educators, policymakers, and practitioners seeking to strengthen digital literacy and advance inclusive digital economies.